The Effect of Human Resource Management on Organizational Productivity Through Employee Satisfaction: A SEM-PLS Approach in InJourney Aviation Service Group - Danang Brahmantyo S; Osly Usman (Journal of Digital Business and Global Economy, 2026)
Abstract This is a quasi-experimental study that aimsto analyze the mediating role of employee satisfaction in athematical approach the impact of human resource management (HRM) on organizational productivity to Injourney AviationService Group. The design is mainly explanatory design and quantitative approach. DATA Data collected from 2025 Employee Satisfaction Survey of 2,166 workers in some work units within the company. SEM-PLS was used for analysis. The study found that HR management positively impacted employee satisfaction (β = 0.812), organizational productivity (β = 0.721), and organizational productivity (β = 0.264). HR management indirectly affects organizational productivity through employee satisfaction, 0.585 more than directly. These findings suggest that employee satisfaction mediates the HR management-organizational productivity relationship. This research provides a theoretical contribution to the development of a job satisfaction-based HR management model as well as practical implications for aviation service organizations in increasing productivity through effective HR management.